Elephants as agents of seed dispersal in Aberdare and Tsavo National Parks, Kenya - John Waithaka (Pachyderm)
This study used two quite different habitats to illustrate the role of the elephant as an agent of seed dispersal: Aberdare NP, a mountainous forest region in central Kenya, and the Tsavo ecosystem which is largely comprised of arid bushland in south eastern part of the country. 18 plant species (15 herbs, 2 shrubs and 1 tree) belonging to 12 families germinated from elephant dung samples obtained in Tsavo. 36 species (27 herbs, 3 shrubs and 6 trees) belonging to 19 families germinated from samples obtained in the Aberdares. Results of the dung analysis and seed germination trials indicate that many plant species are dispersed by elephants, and for some of these species elephant may be the obligate agents of dispersal. Removing elephants from their natural ranges or restricting their movements using electric fences may result in serious implications with far reaching ecological impacts on species diversity in the long term.